1992
DOI: 10.1016/0014-5793(92)81322-d
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate derivatives of AZT display enhanced selectivity of action against HIV1 by comparison to the parent nucleoside

Abstract: Novel phosphate derivatives of the and-HIV nucleoside anulogue AZT have been prepared by phosphorochloridate chemistry. In particular, phosphates carrying ester-containing side-chains are described. These materials arc designed 10 act as membrane-soluble prodrugsof the bio-active free nucleotides. In vitro evaluation revealed the compounds to have a pronounced, selective anliviral activity. In several cases the phosphate derivatives are more seieclive in their aclhl than the parent nucleoside AZT. In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In this report McGuigan stated: “If these in vitro findings could be translated into a demonstrable in vivo advantage, such phosphate pro-drugs could have merit as candidates for clinical development.” 138 This was clearly an anticipation of what would have happened 25 years later. His investigations underlaid the importance of the masked phosphate approach, and had significant implications for what became the future design of chemotherapeutic NAs.…”
Section: Protide Approach Application To Antiviral Nucleosidesmentioning
confidence: 94%
See 1 more Smart Citation
“…In this report McGuigan stated: “If these in vitro findings could be translated into a demonstrable in vivo advantage, such phosphate pro-drugs could have merit as candidates for clinical development.” 138 This was clearly an anticipation of what would have happened 25 years later. His investigations underlaid the importance of the masked phosphate approach, and had significant implications for what became the future design of chemotherapeutic NAs.…”
Section: Protide Approach Application To Antiviral Nucleosidesmentioning
confidence: 94%
“…Continuing to explore different structures, the phosphorus center was then masked with an ester-containing group in combination with either a simple alkyl moiety or a trichloroethyl group or another ester-containing group. 138 The results of these investigations revealed the presence of two ester-substituted groups enhances activity relative to having only one substituted group. Furthermore, suggesting that a trihaloethyl group may substitute for an ester-containing group but with reduced potency.…”
Section: Protide Approach Application To Antiviral Nucleosidesmentioning
confidence: 96%
“…In recent years a similar prodrug approach of nucleotides has been reported. [14][15][16][17][18][19][20] While simple dialkyl phosphotriesters16 of AZT were found to be inactive, haloalkyl l6 and other lipophilic long chain alkyl phosphotriesters 18,19 of AZT showed comparable activity with that of AZT.…”
mentioning
confidence: 84%
“…A number of researchers have demonstrated that the phosphate group on the nucleoside analogs has the potential to be a new antivirus drug with antiviral activity (McGuigan et al 1992). Thus some emphasis has been placed on developing a commercial and simple way of synthesizing the monophosphate derivative of the nucleoside analog (Uckum et al 2005;Kitade 1997).…”
Section: Introductionmentioning
confidence: 99%